2003
DOI: 10.1021/ja036505h
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Synthesis of Soluble and Processable Organic-Capped Anatase TiO2 Nanorods

Abstract: We demonstrate the controlled growth of high aspect ratio anatase TiO2 nanorods by hydrolysis of titanium tetraisopropoxide (TTIP) in oleic acid (OLEA) as surfactant at a temperature as low as 80 degrees C. Chemical modification of TTIP by OLEA is proven to be a rational strategy to tune the reactivity of the precursor toward water. The most influential factors in shape control of the nanoparticles are investigated by simply manipulating their growth kinetics. The presence of tertiary amines or quaternary ammo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

26
854
1
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 934 publications
(887 citation statements)
references
References 101 publications
26
854
1
6
Order By: Relevance
“…Preferential growth of pure TiO 2 nanocrystals along the c-direction has been reported previously, 22 and the ellipticity observed in Figure 2A indicates that it should be possible to generate similarly anisotropic nanocrystals of this DMS from solution under proper experimental conditions. Although TiO 2 nanocrystals are susceptible to aggregation, the lack of noticeable visible-light scattering by the NC1 suspension suggests that little aggregation has occurred in this case.…”
Section: Results and Analysissupporting
confidence: 77%
“…Preferential growth of pure TiO 2 nanocrystals along the c-direction has been reported previously, 22 and the ellipticity observed in Figure 2A indicates that it should be possible to generate similarly anisotropic nanocrystals of this DMS from solution under proper experimental conditions. Although TiO 2 nanocrystals are susceptible to aggregation, the lack of noticeable visible-light scattering by the NC1 suspension suggests that little aggregation has occurred in this case.…”
Section: Results and Analysissupporting
confidence: 77%
“…The absorption peaks , also observed for the particles obtained at 300 and 400 °C, indicated that the NPs contained carboxylate (COO -) groups (Fig. 6) [65][66][67]. In addition, the weight loss of the MARIMO TiO 2 NPs synthesized in the presence of phthalic acid at 300 and 400 °C was 11.5% and 12.0%, respectively, as determined via TG analysis under a N 2 gas flow, indicating that the MARIMO TiO 2 NPs contain at most ca.…”
Section: Resultsmentioning
confidence: 89%
“…Nanocrystals of titanium dioxide (nan-TiO2) were prepared using a hydrothermal method with oleic acid as the surface stabilising ligand. 13 Transmission electron microscopy (TEM) ( Figure 3a) and PXRD showed that the nanoparticles are on average 8.9 ± 1 nm in diameter, single crystalline and exhibit the anatase phase. Combustion analysis gave an oleic acid:TiO2 molar ratio of 1.25:1 and the nanocrystals can be dispersed in common organic solvents to give optically transparent solutions.…”
mentioning
confidence: 99%